2015
DOI: 10.1097/hjh.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Marinobufagenin-induced vascular fibrosis is a likely target for mineralocorticoid antagonists

Abstract: Objective Endogenous cardiotonic steroids (CTS), including marinobufagenin (MBG), stimulate vascular synthesis of collagen. Because mineralocorticoid antagonists competitively antagonize effect of CTS on the Na/K-ATPase, we hypothesized that spironolactone would reverse the pro-fibrotic effects of MBG. Methods Experiment 1. Explants of thoracic aortae and aortic vascular smooth muscle cells (VSMC) from Wistar rats were cultured for 24 hours in the presence of vehicle or MBG (100 nmol/L) with or without canre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 33 publications
2
65
0
Order By: Relevance
“…It was shown that certain inhibitors of Na ϩ -K ϩ -ATPase increase collagen synthesis by cultured rat cardiac fibroblasts, human dermal fibroblasts, or rat vascular SM cells (13)(14)(15)(16). However, these studies have not rigorously examined the effect of these compounds on the expression of myofibroblast differentiation markers, on the magnitude of their effect relative to that of TGF-␤, or on their effect on TGF-␤-induced myofibroblast differentiation.…”
Section: B Cmentioning
confidence: 99%
“…It was shown that certain inhibitors of Na ϩ -K ϩ -ATPase increase collagen synthesis by cultured rat cardiac fibroblasts, human dermal fibroblasts, or rat vascular SM cells (13)(14)(15)(16). However, these studies have not rigorously examined the effect of these compounds on the expression of myofibroblast differentiation markers, on the magnitude of their effect relative to that of TGF-␤, or on their effect on TGF-␤-induced myofibroblast differentiation.…”
Section: B Cmentioning
confidence: 99%
“…There is extensive evidence implicating CS in the pathogenesis of various models of salt‐dependent hypertension and in the potential end‐organ sequelae associated with such elevation of BP . We initiated these studies to determine whether CS might be relevant to BP levels in the widely used SHR model of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…40 Administration of spironolactone to these patients with resistant hypertension for 6 months in addition to the conventional triple anti-hypertensive therapy restores of NKA activity, decreased SBP and DBP, and significantly reduced PWV. These data further demonstrate the intimate relationship of MBG and arterial stiffness.…”
Section: An Age-associated Increase In Renin Angiotensin Aldosterone mentioning
confidence: 91%
“…35,36,37,38,39 Interestingly, compared to normotensive control, older patients with resistant hypertension demonstrate greater blood pressure and PWV, higher plasma MBG (an NKA inhibitor), and decreased erythrocyte NKA activity. 40 In this regard, it is of note that the increase in arterial pressure induced by a chronic high NaCl intake (i.e. salt-sensitive hypertension) in rodents is substantially reduced by an anti-MBG antibody.…”
Section: Salt-sensitive Hypertension and Agingmentioning
confidence: 99%
See 1 more Smart Citation